2007
DOI: 10.1007/s11172-007-0375-7
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of PtBr6 2− in aqueous solution

Abstract: Photochemistry of the PtBr 6 2-complex in aqueous solution was studied by steady state and laser flash photolysis (308 nm). The multistep photoaquation of the complex occurs in the nano and microsecond time intervals without the formation of intermediate platinum(III) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Note that a recent study on the photochemistry of Pt IV Br 6 2À in aqueous solutions [84] supports the hypothesis by Balzani et al [80][81][82] on the multi-stage photoaquation of the complex. The authors re-examined the quantum yields of the first stage, obtaining the value of 0.39 in unbuffered aqueous solutions, 0.29 in pH 6.86 buffer, and 0.6 in 1 M HElO 4 [84].…”
Section: Hexabromoplatinatesupporting
confidence: 83%
“…Note that a recent study on the photochemistry of Pt IV Br 6 2À in aqueous solutions [84] supports the hypothesis by Balzani et al [80][81][82] on the multi-stage photoaquation of the complex. The authors re-examined the quantum yields of the first stage, obtaining the value of 0.39 in unbuffered aqueous solutions, 0.29 in pH 6.86 buffer, and 0.6 in 1 M HElO 4 [84].…”
Section: Hexabromoplatinatesupporting
confidence: 83%
“…The PtBr 6 lysozyme case at progressively increasing X-ray doses we have also studied at room temperature. The stability of PtBr 6 under UV irradiation has been studied and reported in the literature [5]. The X-ray scattering behaviour of these complexes under femtosecond intense X-ray pulse conditions we plan to investigate at an XFEL and for the sub nano second to longer timescales we have plans to utilise ESRF.…”
mentioning
confidence: 99%
“…1 Photochemistry of IrCl 6 2-in organic solvents has been studied in sufficient detail. [2][3][4][5][6][7][8] In alcoholic solutions the primary photoprocess involves the electron transfer from a solvent molecule to the excited complex, resulting in the reduction of the central ion and formation of hydroxyalkyl radicals. [3][4][5][6][7] The stepwise photosolvation of IrCl 6 2-occurs in acetonitrile solutions.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] The stepwise photosolvation of IrCl 6 2-occurs in acetonitrile solutions. 8 The study of photochemistry of aqueous solutions of IrCl 6 2-showed 9-12 that the nature of the products and the quantum yield of photolysis depend on the exciting light wavelength and the concentration of chloride ions in solu tion. 10, 11 The final photolysis products upon excitation in the region of the charge transfer band (254 nm) are the iridium(IV) complex IrCl 5 (H 2 O) -and the iridium(III) complex IrCl 5 (H 2 O) 2-.…”
mentioning
confidence: 99%
See 1 more Smart Citation